A qualitative comparison of parent and childcare provider perceptions of communication and family engagement in children's healthy eating and physical activity. (24th August 2021) - Dinkel, Danae; Rasmussen, Maggie; Rech, John P.; Snyder, Kailey; Dev, Dipti A.
Abstract: Background: Parents and childcare providers play a substantial role in the development of health behaviours among the children they care for. In order to ensure the optimal growth and development of children, communication and family engagement in childcare is critical. Previous studies examining parent or provider perceptions about healthy eating or physical activity have explored these concepts individually and/or have only included only parents or providers. Therefore, the purpose of this study was to compare childcare provider and parent perceptions of communication regarding healthy eating and physical activity as well as use of best practice strategies on family engagement for these topics. Methods: Childcare providers ( n  = 12) in childcare centres or a family childcare home and a parent ( n  = 12) of a child they provide care for participated in a semi‐structured interview guided by the Social Ecological Model. Interviews were transcribed verbatim and uploaded to NVivo for data analysis. Data were analysed using a directed content analysis. Three trained qualitative researchers developed a codebook and then compared responses between parents and providers. Results: Similarities in provider and parent responses included agreement on healthy eating; influences on child development; parents being the most influential on children's healthy eating; how they identified physical activity opportunities; and the use of family engagement principles. Differences that arose included parents' roles in promoting children's physical activity; challenges for parents in promoting healthy eating and physical activity; and providers' encouragement of physical activity. Importantly, few parents mentioned providers were top influences on their child's healthy eating or physical activity. Providers also mentioned having difficult conversations with parents was challenging. Conclusions: Future efforts are needed to (1) help parents understand the providers' role in the development of their child's health behaviours and (2) strengthen efforts to engage families in healthy behaviours outside of childcare facilities.